The use of molecular and physiological approaches to analyse GROUP VII ETHYLENE RESPONSE FACTORS (ERFVIIs) and the PRT6 N-degron pathway - Jones, Dominic (2020)
Vast proportions of the earth are high altitude and mountainous terrain. For successful growth development at high altitude, seedlings must adapt to high altitude conditions in order to survive. The major difference in high altitude terrain to that of sea level is the difference in surrounding oxygen concentration (v/v). Oxygen concentration falls significantly as altitude elevation increases, resulting in an increasingly hypoxic environment. GROUP VII ETHYLENE RESPONSE FACTORS (ERFVIIs) have been shown to responsible for sensing oxygen and are substrates of the PRT6 N-degron pathway of proteolysis. Here, I investigate the adaption to altitude associated with A. thaliana accessions and the impact of growing A. thaliana accessions in a hyperoxic (27%) environment. In addition, I show the role of the RELATED TO APETALA2.3 (RAP2.3) ERFVII in regulating protochlorophyllide (PCH) accumulation following an extended period of darkness and etiolation of the seedling. Furthermore, I develop transgenic tools to enable further analysis of the PRT6 N-degron pathway. Observations show significant differences in responses of accessions to varying growth conditions, and show that altitude adaption is an essential component of ensuring successful growth and survival of seedlings.